INDICADORES AMBIENTAIS DA GLOBAL REPORTING INITIATIVE GRI : uma análise da utilização nos relatórios de sustentabilidade das empresas do setor de energia elétrica - Bessa, Elisio Cesar (2015)
Sustainability reports are an important means of corporate communication with its stakeholders. However, the disclosure of environmental indicators in these reports is still considered low. The GRI sustainability reporting model was designed to help organizations better report their performance in economic, social and environmental areas, but studies show that many companies declared themselves followers of this standard but in practice the disclosure is still low. This study aims to analyze the sustainability reports for the energy sector companies, listed in the Dow Jones Sustainability Index (DJSI), comparing the disclosure of core environmental indicators with GRI standards. For this, it was made an exploratory and documentary research, in the organizations sustainability reports for three consecutive years. It was developed a criteria to classify the indicators as well as an index to represent the company disclosure level, called Environmental Disclosure Index (IEVA). After that, it was made an analysis of all data and information provided by companies in the sample, comparing what was evidenced with what is required by the GRI model, when was possible to observe that despite belonging to the same sector, with the same difficulties and complexities, companies are at different stages of environmental disclosure, regardless of country or geographic region. No organization fully meets GRI model requirements, even those who declared themselves at the highest level of guidelines application. Companies in Europe, have better environmental disclosure, followed by companies from South America, North America and Asia. There is a tendency to improve environmental disclosure in the three years analyzed in this research. An important contribution of this research was the development a method to classify the indicators as well as the calculation of the Environmental Disclosure Index (IEVA) that can be used in other dimensions of sustainability reports and in the analysis of other industrial sectors.